Edukasi Personal Hygiene Pada Anak Usia Taman Kanak-Kanak ‘Aisyiyah 26 Palembang - Widya Arisandy; Meita Hipson; Sri Handayani; Anggun Sri Melani; Wulan Fitra Saskiya Tunnisa (Universitas Baiturrahim, 2026)
Personal hygiene is one of the important aspects in forming clean and healthy living behaviours that need to be instilled from an early age. Children of kindergarten age are in an early developmental phase that is crucial for forming health habits in the future. However, the limitations in understanding, concentration, and the child's ability to practice personal hygiene often become obstacles in its independent application. This community service activity aims to enhance knowledge and skills in personal hygiene among kindergarten-aged children through education and direct practice. The activity was conducted at TK Aisyiyah 26 Palembang with a total of 25 participants, consisting of 15 male students and 10 female students. The methods used included educational outreach, demonstrations of proper handwashing practices, and direct supervision involving two lecturers and two students. The results showed that all the children were able to answer questions after being educated on the importance of personal hygiene, and were able to practice personal cleanliness correctly, such as cutting nails, washing hands, and brushing teeth. Suggestion that this activity is expected to become the foundation for instilling clean and healthy living habits in the school and home environment for children regularly and consistently.